Asymptomatic bacteriuria in pregnant high - Jerí, María (2015)
OBJECTIVES: To determine the incidence and neonatal outcomes of asymptomatic bacteriuria in pregnant women at high altitude. DESIGN: Comparative and prospective study. SETTING: EsSalud’s Southeast national hospital. PARTICIPANTS: Three hundred pregnant women with singletons. INTERVENTIONS: Midstream urine samples for culture were taken from women who had prenatal control at our hospital from January 2002 through December 2004. MAIN OUTCOME MEASURES: Asymptomatic bacteriuria and neonatal outcome. RESULTS: The incidence of asymptomatic bacteriuria was 17,7%. The most common uropathogen isolated was Escherichia coli (71,7%). History of preterm delivery and urine culture in the first trimester showed statistical significance (p< 0,05). Maternal age, route of delivery, weight, gender, gestational age, newborn’s Apgar during the first and fifth minute, relationship between newborn weight and gestational age, type of reanimation, admission unit, reason for neonatal internsive care unit admission, and time of hospitalization did not show statistical significance. CONCLUSIONS: The incidence of asymptomatic bacteriuria is high at high altitude and similar to that at sea level. Pregnant women with history of preterm delivery frequently showed asymptomatic bacteriuria. It seems better to take a urine culture during the first trimester than later.